PERNIKAHAN ADAT JAWA PERSPEKTIF HUKUM ISLAM - Hidayah Jaya Riswanda; Dzulfikar Rodafi; Moh. Muslim (Prodi Ahwal syakhshiyyah Fakultas Agama Islam UNISMA, 2021)
Almost all humans experience a stage of life called marriage. Marriage or marriage is a ceremony for the union of two souls into a family through a contract regulated by religion. Therefore, marriage becomes a great and sacred ceremony.This study examines how the perspective of Islamic law on Javanese traditional marriages is. In marriage, it has been regulated by the Shari'a which starts from the process of proposing to someone to getting married which has been explained in the Shari'a so easily. However, in the Javanese traditional tradition, there are several processions in the implementation of marriage, starting from applying to getting married. So what is the perspective of Islamic law on this matterThis research uses the type of library research, namely